2012
DOI: 10.1175/jcli-d-11-00619.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Use of a Genesis Potential Index for Tropical Cyclones in the North Atlantic Basin

Abstract: Large-scale environmental variables known to be linked to the formation of tropical cyclones have previously been used to develop empirical indices as proxies for assessing cyclone frequency from large-scale analyses or model simulations. Here the authors examine the ability of two recent indices, the genesis potential (GP) and the genesis potential index, to reproduce observed North Atlantic cyclone annual frequency variations and trends. These skillfully estimate the mean seasonal variation of observed cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 67 publications
(72 reference statements)
6
98
1
1
Order By: Relevance
“…Suzuki-Parker (2012) applied the Bruyère et al (2012) index to the same revised global data used to drive the NRCM simulations presented in Section 2 and produced results in agreement with the NRCM dynamical results of an increase in tropical cyclone frequency of between 1 and 3 storms by the mid 21 st century.…”
Section: Empirical Assessments Of Tropical Cyclone Frequencymentioning
confidence: 65%
See 1 more Smart Citation
“…Suzuki-Parker (2012) applied the Bruyère et al (2012) index to the same revised global data used to drive the NRCM simulations presented in Section 2 and produced results in agreement with the NRCM dynamical results of an increase in tropical cyclone frequency of between 1 and 3 storms by the mid 21 st century.…”
Section: Empirical Assessments Of Tropical Cyclone Frequencymentioning
confidence: 65%
“…Bruyère et al (2012) showed that for interannual variability and longer-term changes, the relative humidity and vorticity terms contribute nothing to the skill, though this could be due to the specific formulation of the index rather than having a physical interpretation (a general limitation highlighted by Menkes et al 2011). Bruyère et al (2012) also found care needs to be taken when selecting an index averaging area: for the North Atlantic, a basin-wide average was not optimal in explaining total basin cyclone frequency, whereas an average taken over the eastern tropical Atlantic (5-20 o N, 60-15 o W), was able to explain 72 % of the annual variance of total basin cyclone frequency.…”
Section: Empirical Assessments Of Tropical Cyclone Frequencymentioning
confidence: 99%
“…The proportions have changed consistently with the globe as a whole but the slope is smaller. Since 1995 there has been a marked increase in the annual frequency of North Atlantic tropical cyclones, including intense hurricanes and these are closely aligned with increasing North Atlantic SST [see Bruyère et al (2012) for a detailed discussion], the global balance (Fig. 3a) has been maintained by a corresponding decrease for annual tropical cyclones in the western North Pacific.…”
Section: Hurricane Proportionmentioning
confidence: 99%
“…Warmer sea surface temperatures (SSTs) are favorable to tropical cyclones. However, global warming may also increase vertical wind shear, which is unfavorable for cyclones (3), although some studies find this is a minor effect (4). Dynamical downscaling of Atlantic tropical cyclones tend to show fewer but more intense events, but the results are not consistent between models (5,6).…”
mentioning
confidence: 99%